Attitudes Toward Bile Extraction From Living Bears: Survey of Citizens and Students in Beijing. Issue 3 (3rd July 2017) - Liu, Zhao; Jiang, Zhigang; Yang, Aifang; Xu, Bingbing; Fang, Hongxia; Xie, Zongping; Li, Ning; Li, Chunwang; Meng, Zhibin; Zeng, Yan
ABSTRACT: Bear bile is a traditional Chinese medicine that has been used for millennia. Several arguments support and oppose the use of bear farming in terms of conservation and nonhuman animal welfare. This study involved designing a questionnaire and surveying a random sample of general citizens and college students in Beijing to elicit their attitudes on bile extraction from living bears. Older people and people with lower education levels used more bear bile medicines. In total, 29.47% ( n = 204) of citizens and 23.14% ( n = 81) of students surveyed used bear bile medicine since 1990. Students were less willing to use bear bile medicines than citizens ( p < .05). The level the respondents agreed with the blue side (against the extraction of bile from living bears; anti for short) was significantly higher than that for the red side (support the extraction of bile from living bears; pro for short; p < .05). Additionally, college students had a more distinct attitude toward the opposing views, which indicates they were more inclined to oppose bile extraction from living bears.